Role of the androgen receptor in melanoma aggressiveness - Marzia Di Donato; Costanza Maria Cristiani; Mariaelena Capone; Cinzia Garofalo; Gabriele Madonna; Lucia Carmela Passacatini; Margaret Ottaviano; Paolo Antonio Ascierto; Ferdinando Auricchio; Ennio Carbone; Antimo Migliaccio; Gabriella Castoria (Cell Death and Disease)
Abstract Malignant melanoma represents the fifth most common cancer in the world and its incidence is rising. Novel therapies targeting receptor tyrosine kinases, kinases and immune checkpoints have been employed with a significant improvement of the overall survival and long-term disease containment. Nevertheless, the disease often progresses and becomes resistant to the therapies. As such, the discovery of new targets and drugs for advanced melanoma still remains a difficult task. Gender disparities, with a female advantage in melanoma incidence and outcome, have been reported. Although emerging studies support the pro-tumorigenic role of androgen/androgen receptor axis in melanoma, the molecular bases of such evidence are still under intense investigation. We now report that ligand activation of the androgen receptor drives melanoma invasiveness and its escape from natural killer-mediated cytotoxic effect. By combining different experimental approaches, we observe that melanoma escape is mediated by the androgen-triggered shedding of the surface molecule MICA. Specific blockade of ADAM10 or androgen receptor impairs the androgen-induced MICA shedding and melanoma immune-escape. Further, the increase in MICA serum levels correlates with a poor outcome in melanoma patients treated with the anti-PD-1 monoclonal antibody, pembrolizumab. At last, melanoma cells depleted of the androgen receptor become more responsive to the most commonly used immunocheckpoint inhibitors, suggesting that the receptor dampens the immunotherapy efficacy. Taken together, our findings identify the androgen receptor as a diagnostic guidance in melanoma and support the repositioning of AR blockers in clinical management of patients.